Removal of 200 mg/L of dissolved methyl orange through photocatalysis with TiO2 nanoparticles (2021)
Nearly 80% of wastewater resulting from human activities get directly discharged to natural water streams, polluting the already scarce hydric resource. Water pollution is an acute problem worldwide and a major challenge to treatment technologies. Organic chemical compounds are a significant pollutant in surface water, their presence lead to adverse effects on human health and ecosystems. Traditional methods for wastewater treatment are inadequate to efficiently purify water from organic chemical pollutants. This research focuses on the photocatalytic water treatment using titanium dioxide and ultra-violet radiation to remove methyl orange from water, while establishing which concentrations of titanium dioxide and exposed time to radiation increase degradation of the pollutant. This research aims to provide information that strengthens the field of water treatment and purification through nanotechnology.